Aplicação da Escala-NEP para a Mensuração da Consciência Ecológica de Professores Universitários: perfil e implicações para estudos futuros - Luciana Flores Battistella (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
This study aimed to investigate the environmental awareness of university professors of business administration courses from Brazilian institutions. To this end, we adopted the scale of the New Ecological Paradigm (NEP-Scale) developed by Dunlap and VanLier (1978) and updated by Dunlap et al. (2000). We conducteda survey research to then carry out exploratory factor analysis and descriptive analysis. It was observed that professors have an ecological conscience considered high, with an average of 3.66 for all-NEP scale. As the result, ecological awareness is more evident among women, divorced, having children, are aged 40 to 59 years and have a monthly family income from 2 to 5minimum wages. Through exploratory factor analysis-NEP Scale,with 15 variables before, now has nine variables distributed in the four factors found. The scale had a significant internal consistency, with a Cronbach's alpha of 0.743. The first factor was named anti-anthropocentrism, factor 2 was called Limits to Growth, the third factor received the title of the ecological crisis and the factor 4 is named after rejection of exceptionalism.